Feasibility and reproducibility of the PsAMRIS-H score for psoriatic arthritis in low-field-strength dedicated extremity magnetic resonance imaging. (October 2013) - Strube, H; Becker-Gaab, C; Saam, T; Reiser, M; Schewe, S; Schulze-Koops, H; Treitl, M
Abstract : Objectives: The psoriatic arthritis magnetic resonance imaging scoring system (PsAMRIS-H) for the evaluation of inflammatory and destructive changes in PsA hands was validated on 0.6-T scanners. The applicability of the PsAMRIS-H on a low-field MRI system as a well-accepted, low-cost imaging modality was evaluated. Method: In 65 consecutive patients (31 males, median age 52 years), 73 scans on a 0.2-T dedicated extremity MRI system were obtained for evaluation of PsA. Images were scored for synovitis, tenosynovitis, periarticular enhancement, bone erosion, bone oedema, and proliferation, and the PsAMRIS-H score was calculated. The intraclass correlation coefficient (ICC) was calculated and the paired t-test conducted. Results: Intra-reader reliability for the total PsAMRIS-H score was good, with an ICC of 0.81 and 0.77 for readers 1 and 2, respectively, and inter-reader agreement was moderate (0.57 for each reader). However, the PsAMRIS-H score differed significantly between the two readers (22 vs. 31; p < 0.05). When individual components of the PsAMRIS were evaluated, intra- and inter-reader agreement was poor to moderate, especially for tenosynovitis and periarticular inflammation. Conclusions: Low-field 0.2-T MRI is capable of quantifying the PsAMRIS-H with good intra-reader reproducibility. However, low signal-to-noise ratio (SNR), low spatial resolution, and system artefacts limit the application of the PsAMRIS-H, leading to low inter- and intra-reader agreement for individual features.